Cytokinins: A Genetic Target for Increasing Yield Potential in the CRISPR Era - Mandal, Sayanti; Ghorai, Mimosa; Anand, Uttpal; Roy, Debleena; Kant, Nishi; Mishra, Tulika; Mane, Abhijit Bhagwan; Jha, Niraj Kumar; Lal, Milan Kumar; Tiwari, Rahul Kumar; Kumar, Manoj; Radha,; et al. (Frontiers in Genetics, 2022)
Over the last decade, remarkable progress has been made in our understanding the phytohormones, cytokinin’s (CKs) biosynthesis, perception, and signalling pathways. Additionally, it became apparent that interfering with any of these steps has a significant effect on all stages of plant growth and development. As a result of their complex regulatory and cross-talk interactions with other hormones and signalling networks, they influence and control a wide range of biological activities, from cellular to organismal levels. In agriculture, CKs are extensively used for yield improvement and management because of their wide-ranging effects on plant growth, development and physiology. One of the primary targets in this regard is cytokinin oxidase/dehydrogenase (CKO/CKX), which is encoded by CKX gene, which catalyses the irreversible degradation of cytokinin. The previous studies on various agronomically important crops indicated that plant breeders have targeted CKX directly. In recent years, prokaryotic clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein 9 (Cas9) system has been increasingly used in editing the CKO/CKX gene and phenomenal results have been achieved. This review provides an updated information on the applications of CRISPR-based gene-editing tools in manipulating cytokinin metabolism at the genetic level for yield improvement. Furthermore, we summarized the current developments of RNP-mediated DNA/transgene-free genomic editing of plants which would broaden the application of this technology. The current review will advance our understanding of cytokinins and their role in sustainably increase crop production through CRISPR/Cas genome editing tool.